Sb recovery from an As pre-removed lead anode slime using a ZnS-Na2CO3 smelting reduction (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
The lead anode slime is extensively produced in a lead electrolysis process, in which the Sb content was high to 10-50 wt% and well worth to be recycled. However, in its general alkaline pressure leaching for the As pre-removal, Sb was partially changed to Na3SbO4 with a high stability. It limited the Sb deep reduction and recovery in the followed Na2CO3 smelting reduction. Considering this, ZnS was creatively used as additive to destroy the stable structure of Na3SbO4 and increase the Sb reduction in this research, and meanwhile ZnS was reduced to a volatile Zn (g) and recycled. In a certain range, the increase of coke and ZnS amounts increased the Sb yield, and the Pb recycling could be accelerated. However, as an excessive ZnS added, the Sb compounds could be sulfurized and then combined with the generated PbS and Na2S, producing a sodium matte of Na-Pb-Sb-S. It limited the Sb reduction and decreased the Sb yield. At the optimal condition of coke amount of 13%, ZnS amount of 8%, smelting temperature of 1200 °C and holding time of 90 min, the Sb, Pb and Zn yields achieved up to 97.6%, 95.9% and 98.9% respectively.
Keywords: As pre-removed lead anode slime; Sb recovery; ZnS; phase transformation; smelting reduction